Turnover‐attachment motive of Saudi Arabia nursing workforce: A Cross‐Sectional study - Maria E. M. Mariano; Alexander Woodman; Eidan M. Al Zahrani; Yaser A. Al Naam; Rory R. Farrelly; Lamiaa H. Al‐Jamea; Abbas Al Mutair; Rehab Y. Al‐Ansari; Jenifer V. Quiambao; Jeffhraim Balilla (Wiley, 2023)
Abstract Aim This study aimed to explore the association of turnover‐attachment motive with socio‐demographic data among Saudi and foreign nurses in a hospital in the Eastern Province of Saudi Arabia. Methods A cross‐sectional correlation study was conducted among n = 180 registered Saudi and foreign nurses working at a private tertiary hospital in the Eastern Province, Saudi Arabia. The turnover‐attachment motive survey was used to evaluate the eight motivational forces. Data were analysed using JASP version 16 statistical software and Orange 3 version 3.26.0. The data were subjected to correlation analysis and multiple linear regression. Results Only 8% of participants were identified with a high intention to leave driven by alternative, behavioural, normative and constitutive forces. Younger healthcare workers tend to have higher intentions to quit the job; the 29-33 age group has a statistically significant negative effect, increasing intention to leave. It was found that those with 5-6 years of clinical experience at Dr. Sulaiman Al Habib Hospital, Al Khobar and no experience abroad had statistically significantly lower intention to leave. Conclusion This study presented the factors influencing nursing staff to stay or leave work in a hospital in the Eastern Province of Saudi Arabia that can be a basis for reviewing existing policies and procedures to improve nurses' working conditions.